Psychiatric symptoms are present in most of the patients with idiopathic normal pressure hydrocephalus - Matheus F. Oliveira; João R. M. Oliveira; José M. Rotta; Fernando C. G. Pinto (Arquivos de Neuro-Psiquiatria)
Normal pressure hydrocephalus (NPH) is characterized by gait disturbance, dementia and/or urinary incontinence associated with dilation of ventricular system with normal opening cerebrospinal fluid pressure. Wide scientifical evidence confirms association between NPH and psychiatric symptoms. We selected 35 patients with idiopathic normal pressure hydrocephalus from January 2010 to January 2012 in a Brazilian tertiary hospital and performed a formal psychiatric evaluation to identify psychiatric disorders. Psychiatric disorders were present in 71% of these patients, especially anxiety, depression and psychotic syndromes. NPH patients may develop symptoms with frontal dominance, such as personality changes, anxiety, depression, psychotic syndromes, obsessive compulsive disorder, Othello syndrome; shoplifting and mania. Unusual appearances of NPH symptoms may hinder early diagnosis and consequently proper treatment.